Study on the Position Deviation between the Iron Roughneck’s Spin-Rollers and the Drilling Tool - Yongbai Sha; Quan Li; Xiaoying Zhao (Applied Sciences, 2022)
The spinner mechanism is one of the main working mechanisms of the iron roughneck, which is used to realize the rapid screwing-in or screwing-out of the drill pipe thread. The main problems of the spinner mechanism and the existing solutions are analyzed in this paper, and the spinner mechanism driven by a single hydraulic cylinder and transmitted by a wedge plate is designed. The upper and lower drilling tools are not concentric and affect the spin effect when the spinner mechanism works, and to address this problem, the influence of deviation in different directions is analyzed, and it is proposed that the lateral position deviation of drilling tools is the key factor affecting the spin performance. The relationship between the position deviation of the spin-roller and the position deviation of the drilling tool is established and solved. A method to reduce the lateral position deviation of drilling tools is proposed, and the effectiveness of this method is verified by experiments. The analysis shows that a spinner mechanism with a single follow-up roller easily causes the lateral position deviation of the drilling tool; the deviation of the spin-roller increases with the increase of the lateral deviation of the drilling tool, and the increase of the longitudinal deviation is more obvious; and with the increase of the drilling tool’s diameter, the deviation increases further. The symmetrical double follow-up roller structure can effectively reduce the lateral deviation of drilling tools and spin-rollers and ensures centering performance and the realization of reliable spin.